Early prediction of post cesarean section infection using simple hematological biomarkers: A case control study. (February 2020) - Rotem, Reut; Erenberg, Miriam; Rottenstreich, Misgav; Segal, David; Yohay, Zehava; Idan, Inbal; Yohay, David; Weintraub, Adi Y.
Abstract: Objective: We aimed to investigate whether the neutrophil to lymphocyte ratio (NLR) may assist in the prediction of post CS infections. Study design: This was a case control study performed at the Soroka University Medical Center, a large tertiary teaching medical center, between the years 2012–2016. Cases (post CS infection) were matched to controls (without post CS infection) in a proportion of 2:1. Matching was done according to surgery setting (elective vs. urgent) and date of surgery. Various demographic, clinical and obstetrical characteristics were collected. Laboratory tests that were taken 6−24 h postoperatively were compared between the study groups. Univariate analysis was followed by a multivariate one. Area under the curve was calculated for selected indices. Results: During the study period 113 patients who developed postoperative infection were compared with 224 healthy controls. Among patients in the study group, 71.7 % were diagnosed with surgical site infection, 7.1 % with endometritis and 21.2 % with other infections. Total neutrophil and lymphocyte counts were significantly higher among patient in the study group. NLR as well as platelet to lymphocyte (PLR) ratio were significantly higher among patients during the first 24 postoperative hours. NLR and PLR were found to be independently associated with post CS infection controlling for surgery length, use of hemostatic agents/adhesion barrier and skin closure technique (aOR 1.11 95 % CI 1.06–1.17, aOR 1.004 95 % CI 1.001–1.006, respectively). A performance analysis for NLR showed an area-under-the receiver operating curve (AUC) of 67 % ( P = 0.006). Conclusion: NLR is an easy readily available tool that may have a predictive value in early detection of post CS infection. Further studies are needed in order to support our findings before clinical implications of these findings can be recommended.